Multi-target neuroprotection by dl-PHPB in APP/PS1 mice: a proteomic analysis - Sun, Yingni; Bai, Guoliang; Yang, Kangmin; Feng, Yong; Sun, Hongmei; Xian, Li; Gao, Hongwei (Frontiers in Pharmacology, 2025)
IntroductionDl-PHPB [potassium 2-(1-hydroxypentyl) benzoate] demonstrates robust neuroprotective effects in preclinical models of Alzheimer’s disease (AD), significantly ameliorating cognitive deficits and pathological hallmarks. However, the underlying mechanism remains largely unclear. The current study primarily focused on elucidating dl-PHPB’s neuroprotective mechanisms and identifying potential targets in preclinical AD models.MethodsComparative proteomic analyses were performed on APP/PS1 mice orally administered either dl-PHPB (30 mg/kg) or vehicle daily for 3 months, alongside vehicle-treated wild-type (WT) non-transgenic littermates as controls. Total proteins were separated using two dimensional difference gel electrophoresis, and differentially expressed protein spots were identified via LC‐MS/MS.Results and discussionOur results revealed 11 altered proteins in the cortex and 10 in the hippocampus between the WT and APP/PS1 groups treated with vehicle. Following dl-PHPB treatment, 12 differentially expressed proteins were identified in the cortex and 9 in the hippocampus of APP/PS1 mice. These proteins are primarily involved in energy metabolism, neuronal structure, protein trafficking, inflammatory and oxidative responses, and amyloid β (Aβ) and Tau processes, among which several proteins were validated as potential therapeutic targets. Notably, the expression levels of cofilin-2 and VDAC1 in APP/PS1 mice were restored to near-normal levels by the treatment with dl-PHPB, memantine, or donepezil, and further clinical validation is required to establish their utility as AD biomarkers for therapeutic efficacy.